The Netter presenter human physiology collection - Hansen, John T. (Teterboro, NJ : Icon Learning Systems, 2003)
Human physiology images from Netter's atlas of human physiology, ready for export to your presentation software
Systems requirement: Windows; any IBM-compatible PC with a monitor of at least 1024 x 768 pixed resolution displying 43-bit color depth or more. Windows 98, ME, 2000, and XP are supported. A minimum of 64 MB of RAM for Windows 98 and a minimum of 256 MB for Windows XP are highly recommended. The Netter Presenter runs best on a pentium processor running at 400 MHz or faster
Keywords: Human, Anatomy -- atlases